1990
DOI: 10.2118/16031-pa
|View full text |Cite
|
Sign up to set email alerts
|

Partially Decoupled Modeling of Hydraulic Fracturing Processes

Abstract: >SDE \/01)31Sum......,. A new method of partial decoupling of the problem of modeling a hydraulic fracture in a reservoir is described. This approach has significant advantages over previous methods with either fully coupled or completely uncoupled models. Better accuracy can be achieved in modeling the fracture propagation, and the new system is very efficient and versatile. Virtually any reservoir model can be used for predicting postfracture productivity. Examples of single-and multiphase applications for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The discrete approach involves some computational disadvantages. For instance, fracturing increases the number of nodes and changes the topological connectivity of the mesh, which creates significant challenges for automating the approach (Suidan and Schnobrich 1973;Bažant and Oh 1983). Even though the smeared-fracture approach does not fully represent the physical nature of a crack, it is an alternative to the discrete-fracture method because it enables the simulation of fracture branching, fracture rotation, and multiple shear and tensile fractures in unpredetermined directions.…”
Section: Smeared-fracture Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrete approach involves some computational disadvantages. For instance, fracturing increases the number of nodes and changes the topological connectivity of the mesh, which creates significant challenges for automating the approach (Suidan and Schnobrich 1973;Bažant and Oh 1983). Even though the smeared-fracture approach does not fully represent the physical nature of a crack, it is an alternative to the discrete-fracture method because it enables the simulation of fracture branching, fracture rotation, and multiple shear and tensile fractures in unpredetermined directions.…”
Section: Smeared-fracture Approachmentioning
confidence: 99%
“…Modelling a fracture using a numerical method with the element size equal to the fracture thickness will result in a fine mesh because of the typically small aperture size compared with the model size, rendering engineering problems computationally impractical (Settari et al 1990;Weill and Latil 1992). It has been demonstrated that a fracture can be included in much larger elements, provided that an equivalent permeability of the element is determined from the average of the matrix permeability and the fracture conductivity (Settari et al 1990;Weill and Latil 1992;Ji 2008).…”
Section: Smeared-fracture Approachmentioning
confidence: 99%
“…Settari et al (1990) were the first to propose the concept of partially decoupled fracture modeling. They linked a fracture simulator, a fluid flow simulator and a proppant simulator together and mapped the fracture geometry and proppant concentration in terms of permeability and porosity onto the reservoir simulator grids.…”
Section: Introductionmentioning
confidence: 99%
“…They linked a fracture simulator, a fluid flow simulator and a proppant simulator together and mapped the fracture geometry and proppant concentration in terms of permeability and porosity onto the reservoir simulator grids. To better capture the discontinuous front of proppants inside the fracture, Settari et al (1990) used a finer finite difference grid (finer than the grids used in the fracture and fluid flow modules) for solving the one-dimensional PDE of the proppant transport model. Later, several researchers used this approach in their numerical simulation of proppant transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation